Review Article about Environmental Waste Recycling and Environmental Security - Alwan, Haider Salam; Mohammed, Abbas Hekmat Majeed; Mohammed Ali, Zainab Ali; Algburi, Muhammed Shakir Hamad (American Journal of Biology and Natural Sciences, 2025)
Waste recycling plays a crucial role in enhancing environmental security by reducing pollution, conserving natural resources, and promoting sustainable development. Despite growing awareness of its benefits, many countries still face challenges in implementing effective waste management strategies. This review examines the environmental, economic, and social dimensions of waste recycling, highlighting its impact on reducing pollution, lowering production costs, and generating employment opportunities. Through an analysis of existing studies, this research identifies key factors influencing recycling efficiency and proposes solutions for improving waste management practices. The findings suggest that integrating recycling into national policies can significantly enhance environmental security and economic sustainability. This study underscores the need for increased public awareness, governmental support, and technological advancements to optimize recycling processes.